Triazole-linked anthracenyl-appended calix[4]arene conjugate as receptor for Co(II): synthesis, spectroscopy, microscopy, and computational studies - Mummidivarapu, V. V. Sreenivasu; Hinge, Vijaya Kumar; Tabbasum, Khatija; Gonnade, Rajesh G.; Rao, Chebrolu P. (Journal of Organic Chemistry, 2013)
A new triazole-linked anthracenyl-appended calix[4]arene-1,3-diconjugate (L) has been synthesized and characterized, and its single crystal XRD structure has been established. Binding properties of L toward different biologically relevant metal ions have been studied by fluorescence and absorption spectroscopy in ethanol. L exhibits selective recognition of Co2+ and can detect down to a concentration of 55 ppb (0.92 mu M). The roles of the calix[4]arene platform as well as the preorganized binding core in L's selective recognition have been demonstrated by studying appropriate control molecules. The mode of binding of L with Co2+ has been modeled both by DFT and MD computational calculations. L and its Co2+ complex could be differentiated on the basis of the nanostructural features observed in AFM and TEM.